2014
DOI: 10.5194/acp-14-12455-2014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of gaseous methylamines in the global atmosphere: impacts of oxidation and aerosol uptake

Abstract: Abstract. Gaseous amines have attracted increasing attention due to their potential role in enhancing particle nucleation and growth and affecting secondary organic aerosol formation. Here we study with a chemistry transport model the global distributions of the most common and abundant amines in the air: monomethylamine (MMA), dimethylamine (DMA), and trimethylamine (TMA). We show that gas phase oxidation and aerosol uptakes are dominant sinks for these methylamines. The oxidation alone (i.e., no aerosol upta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 40 publications
(63 reference statements)
6
93
1
Order By: Relevance
“…A CTM incorporating advanced particle microphysics is one potential option (Yu and Luo, 2014). Such a modeling approach, incorporating interactions with mineral dust and sea salt, has not yet been fully explored in East Asia and is a future research direction.…”
Section: Fine-mode No −mentioning
confidence: 99%
“…A CTM incorporating advanced particle microphysics is one potential option (Yu and Luo, 2014). Such a modeling approach, incorporating interactions with mineral dust and sea salt, has not yet been fully explored in East Asia and is a future research direction.…”
Section: Fine-mode No −mentioning
confidence: 99%
“…14 More generally, amines have attracted increasing attention due to their potential role in enhancing aerosol nucleation rates in the lower troposphere. 15 Because low-molecular weight amines are highly water-soluble, a few studies have been devoted to their interaction with liquid water in order to better characterize their likely dissolution in aqueous aerosols at high temperature, and thus their gas/particle partitionning. [14][15][16] By contrast, very little is known about their interaction with ice surfaces as encountered in high-altitude cirrus clouds or snow flakes.…”
Section: Introductionmentioning
confidence: 99%
“…15 Because low-molecular weight amines are highly water-soluble, a few studies have been devoted to their interaction with liquid water in order to better characterize their likely dissolution in aqueous aerosols at high temperature, and thus their gas/particle partitionning. [14][15][16] By contrast, very little is known about their interaction with ice surfaces as encountered in high-altitude cirrus clouds or snow flakes. As a consequence, the thermodynamic and kinetic properties of amines in the atmosphere are not well quantified and only few atmospheric models incorporate them although they are ubiquitous.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, numerical models can be useful in simulating the distributions of amines on regional or global scales. To our knowledge, only three modeling studies of amines have been reported in the literature, all on a global scale (Myriokefalitakis et al, 2010;Yu and Luo, 2014;Bergman et al, 2015). Myriokefalitakis et al (2010) investigated the potential contribution of amines 20 emitted from oceans to secondary organic formation (SOA) formation, assuming total amine emissions to be one-tenth of the oceanic ammonia emissions.…”
Section: Introductionmentioning
confidence: 99%